2022
DOI: 10.1002/advs.202204315
|View full text |Cite
|
Sign up to set email alerts
|

Direct Formation of Hard‐Magnetic Tetrataenite in Bulk Alloy Castings

Abstract: Currently, predominant high-performance permanent magnets contain rare-earth elements. In the search for rare-earth-free alternates, body-centered tetragonal Fe-Ni is notable. The ordering to form this phase from the usual cubic close-packed Fe-Ni is understood to be possible only below a critical temperature, commonly accepted to be 593 K. The ordering is first demonstrated by using neutron irradiation to accelerate atomic diffusion. The tetragonal phase, designated as the mineral tetrataenite, is found in Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…The relative areas within the overall spectrum corresponding to the three phase types, equivalent to their relative volume fractions, were determined as 66% ± 5% L1 0 , 17% ± 10% A1 and 17% ± 5% PM. This value for the volume fraction of the L1 0 phase is among the highest reported for FeNi alloys, and the highest for naturally occurring FeNi [29]. The angle between ⃗ k γ and B hf , where B hf is taken as the average for the L1 0 and A1 phases, was found to be Θ = 49 • ± 5 • for this measurement, see figure 16.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…The relative areas within the overall spectrum corresponding to the three phase types, equivalent to their relative volume fractions, were determined as 66% ± 5% L1 0 , 17% ± 10% A1 and 17% ± 5% PM. This value for the volume fraction of the L1 0 phase is among the highest reported for FeNi alloys, and the highest for naturally occurring FeNi [29]. The angle between ⃗ k γ and B hf , where B hf is taken as the average for the L1 0 and A1 phases, was found to be Θ = 49 • ± 5 • for this measurement, see figure 16.…”
Section: Resultsmentioning
confidence: 51%
“…However, the disordered-fcc A1 parent phase (space group 225, Fm 3m) is very close in energy to that of the L1 0 phase, and the kinetics of formation of the ordered phase is very slow [26]. FeNi in the L1 0 phase can be synthetically produced [27][28][29] in ultra-thin film form but a consistent large-scale synthesis method has not yet been demonstrated.…”
Section: Meteoritic Feni Phase Analysismentioning
confidence: 99%
“…Notably, the materials of this current study do not contain large amounts of metalloid alloying additions, such as phosphorus and carbon, as were utilized in other works that reported synthesis of tetrataenite. [18,50,51] Preliminarily speaking, the combination of stress and magnetic field applied in-situ during thermal treatment has accomplished in 6 weeks what Nature requires millions of years to achieve. As the lattice diffusivity of the FeNi equiatomic composition has been reported as ≈1 × 10 −27 cm 2 s −1 at T = 573 K, [52] the process utilized in this work is estimated to accelerate diffusion by ten or more orders of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Other authors demonstrated epitaxial thin-film growth by alternate monoatomic layer deposition on suitable substrate buffer layers. [12,13] A very recent and successful effort to form hard-magnetic tetrataenite by bulk alloy casting has been reported by Ivanov et al [14] .…”
Section: Introductionmentioning
confidence: 99%